The unseen patient: competing priorities between patients and providers when cannabis is used in pregnancy, a qualitative study - Gould, Erin E.; Ganesh, Siddhi S.; Nguyen, Ryan Mikeala; Breton, Carrie V.; Bastain, Theresa M.; Dunton, Genevieve F.; Ceasar, Rachel Carmen (Frontiers in Global Women's Health, 2024)
Abstract Objectives: This study aimed to explore competing priorities when cannabis is used during pregnancy from the perspective of providers and Black and Latina people. Maternal cannabis use is increasingly common, but patients and providers alike struggle to navigate it. Methods: This pilot used qualitative, constructivist ground theory methods to conduct semi-structured, remote interviews between November 16, 2021, and February 7, 2022 with 7 Black and Latina people who used cannabis during pregnancy, and 10 providers between March 15, 2022, and April 6, 2022, all of who were in Southern California, U.S. Results: We identified three main findings: 1) Providers reported barriers to caregiving and relationship building with patients due to maternal cannabis use stigma, 2) Providers prioritized the fetus despite patients' current health system challenges that drove cannabis use, and 3) Both patients and providers engaged in personal research beyond the healthcare system to better understand maternal cannabis use. Discussion: Our findings indicate that challenges exist between people who use cannabis during pregnancy and providers. Both groups need accurate, sociocultural sensitive information about maternal cannabis use via a harm reduction lens.